The assessment of the knowledge and awareness about glaucoma in glaucoma patients and general population: a sample from Turkey - Dağtekin, Gökçe; Demirtaş, Zeynep; Soysal, Aziz; Yildirim, Nilgün; M. Önsüz, Fatih; Metintaş, Selma (International Journal of Research in Medical Sciences, 2017)
Background: The study aimed to evaluate the level of knowledge and awareness of glaucoma and their possible determinants in a group of people diagnosed with glaucoma and in a population based group without glaucoma. Methods: The study included people with an age range of 40 to 80years; 410 patients without glaucoma who admitted to primary health care service and 113 patients who admitted to hospitals with diagnosis of glaucoma. In addition to Glaucoma Knowledge Level Questionnaire (GKLQ), participants were asked about their socio-demographic characteristics, level of awareness and resources of the information about glaucoma. Multivariate logistic regression and multiple linear regression analyses were used to assess the variants which have impact on the level of the awareness about glaucoma and to evaluate the factors effective on the score of GKLQ, respectively. Results: The ratio of awareness about glaucoma was found to be 64.1% in people without glaucoma. The knowledge and awareness about glaucoma were found to be higher in glaucoma patients compared to healthy people but not at a desired level. The education level was the only factor effecting both awareness and knowledge about glaucoma. Conclusions: As awareness about glaucoma can lead to early detection, the assessment of the knowledge and awareness about glaucoma is very important in terms of disease prevention. Health education and preventive health care services should be programmed including for both glaucoma patients and healthy people based on the level of their education.